THE ROLE OF LEADERSHIP AND EFFECTIVE STRATEGIC PLANNING FOR NEWS MANAGERS IN RADIO AND TELEVISION IN ENHANCING PERFORMANCE AND RAISING THE EFFICIENCY OF WORKERS IN NEWSROOMS: THE ROLE OF LEADERSHIP AND EFFECTIVE STRATEGIC PLANNING FOR NEWS MANAGERS IN RADIO AND TELEVISION IN ENHANCING PERFORMANCE AND RAISING THE EFFICIENCY OF WORKERS IN NEWSROOMS (Iraqi Journal of Market Research and Consumer Protection, 2023)
The research deals with the role of leadership and effective strategic planning for news managers in radio and television in enhancing performance and raising the efficiency of newsroom workers. Leadership in establishing a culture of creativity, and the study was conducted on a sample of (123) workers in media institutions operating in Iraq and registered with the Media and Communication Commission. Respondents, as for the axis of measuring and managing creativity and raising efficiency by the administration of newsrooms, which encourages individual work and the participation of cadres in making decisions and developing creative ideas, the measurement ratio between two categories is large and very large, and the measurement of the third axis related to establishing a culture of creativity The goal of effective change is large, especially with regard to building a work environment conducive to creativity and encouraging freedom of opinion at an average rate.